2021
DOI: 10.1097/bpo.0000000000001917
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Tomosynthesis in Assessing Accurate Medial Epicondyle Fracture Displacement as Compared With Conventional Radiography and Computed Tomography

Abstract: Introduction: Medial epicondyle fracture displacement is notoriously difficult to determine on conventional radiography, and follow-up computed tomography (CT) is often obtained to measure precise displacement. Another option for fracture characterization is digital tomosynthesis (DT), a technology providing high in-plane resolution of bony anatomy by acquiring multiple low-dose images in a linear arc. Advantages of DT include lower radiation exposure and lower cost than CT, rapid image acquisition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Given this ambiguity, CT imaging can inform the decision for surgical or nonsurgical treatment for some with medial epicondyle avulsion fractures. A 2019 study by Onay et al 1 showed that CT was "superior to determine the real amount of the fracture displacement and was relevant for treatment decision of pediatric medial epicondyle fractures". They also found "better interobserver agreement for axial CT scans relative to treatment decision".…”
Section: To the Editormentioning
confidence: 99%
See 4 more Smart Citations
“…Given this ambiguity, CT imaging can inform the decision for surgical or nonsurgical treatment for some with medial epicondyle avulsion fractures. A 2019 study by Onay et al 1 showed that CT was "superior to determine the real amount of the fracture displacement and was relevant for treatment decision of pediatric medial epicondyle fractures". They also found "better interobserver agreement for axial CT scans relative to treatment decision".…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the recent publication by Livingston et al1 Livingston et al1 stated that computed tomography (CT) has become the preferred method for evaluating medial humeral epicondyle fracture (MHEF) displacement, quoting Onay et al,2 despite the latter authors2 neither having recommended routine use of CTs, nor having reported the use of CTs for the assessment of MHEFs after November 2014. Pezzutti et al’s3 systematic review contradicts Livingston et al’s1 statement, with 35 of 37 papers not having mentioned the use of CTs, one paper reported the use of CT in 8 patients of 32 MHEFs with an incarcerated fragment of which 4 CTs were not necessary to make the diagnosis and one paper which stated that internal oblique radiographs (IOXR) at least approximated the amount of true anterior displacement as seen on CT. None of the authors used digital tomosynthesis (DT). Livingston et al1 quoted Gottschalk et al,4 stating that conventional radiography has poor intraobserver and interobserver reliability.…”
mentioning
confidence: 99%
See 3 more Smart Citations